The Linguistic Landscape of Gender in Vietnamese Personal Names - Nguyen-Viet Khoa (Names)
This study delves into the social gender dynamics embedded within Vietnamese personal names and highlights their significance as indicators of cultural identity and societal norms. Vietnamese naming conventions display distinct gender markers that mirror cultural expectations and familial roles. Using firsthand archival data compiled from the 2006 high school and university entrance examinations, encompassing nearly one million names, this research addresses how gender distinctions are integrated into Vietnamese personal names and identifies the specific linguistic and cultural characteristics that differentiate male and female names. It also considers the historical, cultural, and social influences shaping naming patterns across generations. By analyzing the structure of Vietnamese names, such as gender markers, middle names, and compound names, the study reveals the intricate gender representations within Vietnamese naming practices. Ultimately, this research enhances our understanding of how names encapsulate the interplay between gender, culture, and identity in Viet Nam.